ANALISIS DAN PERANCANGAN E-COMMERCE PADA KOPPI JAMBI - Marsella, Agnes; Gustinar, Gustinar; Nugraha, Hafiz (Jurnal Informatika, Sistem Informasi dan Kehutanan (FORSINTA), 2024)
At this time the development of technology is increasingly advanced, and everything cannot be separated from technology, the need for fast, precise and accurate information is very important in the era of globalization, and from the research conducted several weaknesses were found, among others, product sales are still carried out conventionally, namely by coming to the place, thus narrowing the range of sales and resulting in less than maximum profit. The purpose of this research is to identify problems in the current system and design a android system at Koppi Jambi. When conducting research, the author uses qualitative methods that collect data through interviews, research, and observation based on field events. The analysis method in this study uses the Unified Modeling Language (UML) method . The design design is only limited to a prototype. The results of this research. The final result of the design produces a android e-commerce Information System at Koppi Jambi. With this e-commerce system, it is hoped that it can increase their promotion and sales. help in increasing the number of customers.